Biological treatment in Crohn’s disease - Pawlik, Magdalena; Milewski, Janusz; Rydzewska, Grażyna (Przewodnik Lekarza/Guide for GPs, 2005)
Crohn’s disease is one of the inflammatory bowel diseases. Causal therapy is unknown and effects of conventional therapy are not satisfactory. Biological therapy is indicated for treatment of refractory Crohn’s disease and for reduction in the number of draining fistulas in fistulizing Crohn’s disease.